2011
DOI: 10.1080/00036846.2010.498355
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric farm–retail price transmission and market power: a new test

Abstract: A finite mixture model is used to estimate farm-retail price transmission in the US fresh strawberry market. Results suggest two distinct pricing regimes associated with off-and peak-harvesting seasons. The market power parameter is significant in the peak-harvest regime, but not in the off-peak regime. Moreover, price changes are transmitted completely throughout the marketing channel in the off-peak regime when the market power parameter is zero, but not in the peak-harvest regime when the market power param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 34 publications
0
18
0
3
Order By: Relevance
“…The results are shown using a 2SLS estimator to control for endogeneity problems. This approach has the advantage, as noted by Acharya et al (), of avoiding some of the disadvantages of many studies in the recent literature that focus on the time‐series properties of the data such that it is sometimes unclear whether rejection of symmetry is not simply due to specification error. The instruments used are variations in rainfall, temperature, climate disasters and cloud cover in other geographic regions.…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown using a 2SLS estimator to control for endogeneity problems. This approach has the advantage, as noted by Acharya et al (), of avoiding some of the disadvantages of many studies in the recent literature that focus on the time‐series properties of the data such that it is sometimes unclear whether rejection of symmetry is not simply due to specification error. The instruments used are variations in rainfall, temperature, climate disasters and cloud cover in other geographic regions.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between market power and price transmission has been modelled in the price transmission literature (see for instance, Acharya et al, 2011;Verreth et al, 2015). However, to our knowledge, this paper is the first to model theoretically the relationship between both types of transmission and market power.…”
Section: Introductionmentioning
confidence: 99%
“…Price transmission analysis identified sources of asymmetries, for example, significant fixed costs, adjustment costs, inventory management and perishable products (Meyer and Cramon-Taubadel, 2004, Vavra et al 2005, Fernandez and Crespo 2010, Acharya et al 2011, Felis and Garrido 2015. Other studies underlined the role of agriculture policies in mitigating bargaining power imbalances , Cacchiarelli Sorrentino 2013, Ciliberti Frascarelli 2013 or looked at the possible role of POs to counterbalance market power exertion (Cacchiarelli Chiavicchioli Sorrentino 2016).…”
Section: Imperfect Price Transmission Along the Food Chainmentioning
confidence: 99%
“…In particular, it has been demonstrated that through pooling their agricultural output, farmers may strengthen their bargaining power vis-à-vis potential buyers and input suppliers, reduce risks associated with farming activities, gain market access to particular marketing channels and benefit from economies of scale. As member of producer's organisations (POs) farmers may be able to invest collectively in assets or services requiring high fixed costs allowing them, for instance, to access new technologies and to improve efficiency and productivity, which ultimately lead to higher income (Acharya, Kinnucan, Caudill 2011;Carrau, 2014;McCorriston, 2002;Russo Goodhue Sexton, 2011, Van Heck 2014.…”
mentioning
confidence: 99%